A Case Report of Management of Intestinal Obstruction in a Patient with Situs Inversus Abdominalis (Global Journal of Medical Research, 2023)
Situs inversus totalis is a rare congenital malformation that results in mirror positioning of the thoracic and abdominal organs. Situs inversus abdominalis is a right-left inversion limited to the abdomen; The association of situs inversus with intestinal band occlusion is infrequent; We report a case of acute intestinal obstruction associated with situs inversus abdominalis, the diagnosis was confirmed by abdominopelvic CT scan, and the treatment consisted of a gallbladder resection with anastomosis, with good postoperative results.
Keywords: situs inversus abdominalis; congenital anomaly; Intestinal obstruction; Surgery